Health care access and smoking cessation among cancer survivors: implications for the Affordable Care Act and survivorship care - Burcu, Mehmet (J Cancer Surviv, 2015)
PURPOSE: The study objectives are to examine prevalence of current smoking, and to assess the association of both health insurance (HI) and access to care with smoking cessation among cancer survivors. METHODS: We performed an analysis from a cross-sectional study of cancer survivors aged 18–64 years using nationally representative data from the 2009 Behavioral Risk Factor Surveillance System survey. We assessed the prevalence of current smoking among cancer survivors. Also, in a subset excluding never smokers, we assessed cessation status of cancer survivors operationalized as comparing current to former smokers. RESULTS: The study population (N=18,896) was predominantly 45–64 years of age, female, and white. The prevalence of current smoking was substantially greater among cancer survivors without HI (40.9 %) than for those with HI (19.5 %). Cancer survivors with no HI had 2-fold greater adjusted odds of not quitting cigarette smoking compared to those with HI. Among those with insurance, cancer survivors who did not have regular health care provider or could not see doctor due to cost or had their last routine checkup ≥1 year ago had 60–80 % fold greater adjusted odds of not quitting cigarette smoking compared to cancer survivors who had better access to health care. CONCLUSIONS: Cancer survivors without HI have substantially greater current smoking rates compared with those with HI. Among cancer survivors with HI, those who experienced health care access-related problems had lower cessation rates than their counterparts. IMPLICATIONS FOR CANCER SURVIVORS: Smoking cessation needs to be recognized as a crucial component of preventive care for cancer survivors. Continuous patient engagement and cancer-patient-centered strategies are urgently needed to achieve optimal results for quit rates particularly for young cancer survivors who are most susceptible to current smoking.